The Ethics of the Anti-War Letter and Poetics of Testimony in Tvrtko Kulenović’s History of Illness (1994) - Spahić, Elmir (Context: Journal of Interdisciplinary Studies, 2022)
Tvrtko Kulenović’s History of Illness (1994) belongs to the anti-war letter and poetics of testimony genres from late 20th-century Bosniak and Bosnian-Herzegovian literature. Although a novel, History of Illness depicts the evils of the 1992–1995 war, in which Sarajevo was besieged by the Yugoslav People’s Army and the Army of Republika Srpska. Kulenović writes from the position of victim, and advocates the idea of ethical engagement during the writing process, in which the narrative and existential selves merge. This paper uses the methodological bases of ethical literary criticism to prove the ethical dimension of the literary text.